PENGARUH PERPUTARAN ARUS KAS DAN PIUTANG TERHADAP PROFITABILITAS PT WINTERMAR OFFSHORE MARINE (STIE Rajawali Purworejo, 2018)
The purpose of this study is to determine the positive and significant influence between cash flow turnover and receivables to profitability. This study uses data analysis methods, multiple regression, coefficient of determination t test and F test. Based on the research that the authors do with the calculation using SPSS progam known research results obtained from the value of multiple correlation relationship between cash flow turnover and receivables to profitability of 0.914 and 0.919, which means the relationship of each variable is very strong. While the result of multiple regression analysis yields the equation Y = -0,064 + 0,006 X1 + 0,024 X2. Based on the calculation of coefficient of determination obtained the result that the effect of cash turnove r and receivables to profitability of 87.8%. Test t, generated value of t arithmetic for cash and receivable turnover respectively of 1.755 and 1.833 where t arithmetic <t table. So there is no significant influence between cash flow turnover and receivabl es to the level of profitability. Based on calculation result for f obtained f count equal to 15,375 while f table equal to 19,00. Therefore f arithmetic <f table then it can be concluded that simultaneously there is no positive and significant influence between cash turnover and receivables to profitability.